„odtwarzając z ognia / ciebie, mój tekst”. Dwa wiersze Stanisława Barańczaka – o stwarzaniu i czytaniu drogich drugich - Biedrzycki, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is a comparative analysis of two poems by Stanisław Barańczak: Bez poprawek [Without Corrections] from his debut collection Facial Corrections (Korekta twarzy) and She Cried That Night, but Not for Him to Hear (Płakała w nocy, ale nie jej płacz go zbudził) from his last collection Surgical Precision (Chirurgiczna precyzja). The subject of both these poems is love. In the first one, the erotic poem takes a surprising turn when the punchline reveals the object of feelings to be a text. It opens the reading proposed in the title, according to which the love described by Barańczak is turned into a text, a story, an emotional relationship between two people mediated by language, mutual interpretation and, as a final consequence, by poetry. The article discusses whether transferring feelings into a text is a necessary consequence of the textual nature of one’s presence in the world, whether it results in this tragic alienation of even the closest people or – quite the contrary – whether it allows one to break through the individuality.